Development and Characterization of Nano-Particle Embedded Soy Protein Isolate Films - Gautam, Rakesh B.; Kumar, Satish (International Journal of Bio-resource and Stress Management, 2023)
Most of the Food packaging is non-degradable, which is responsible for environmental pollution. Different types of biopolymers have been exploited to develop materials for eco-friendly food packaging. However, the use of biopolymers has been limited because of their usually poor mechanical and barrier properties, which may be improved by adding reinforcing compounds (fillers), strengthen materials present poor matrix–filler interactions, which tend to improve with decreasing incorporating materialsize. The naturally renewable biopolymers have attracted much attention because of the high potential use as edible and biodegradable films for food packaging. Biodegradable-soy protein isolate-glycerol-Titanium dioxide (TiO2) blend films were developed and characterized as a function of different sonication levels (0, 20 40, 60, 80 and 100%). Results showed that the water vapour permeability, moisture content, moisture absorption and water solubility decreased with increasing sonication level. Mechanical tests revealed the plasticizing effect of nano-particles on the bio-film. At higher pH level improves barrier properties as well as mechanical properties. Increasing pH level from 8-10 the elongation at break and barrier properties showed good results. The final films had an opaque appearance because of presenting titanium di-oxide as strengthen material in developed biopolymeric film. Physical properties (viz., Area, thickness of film) of soy protein showed improved with increasing sonication levels as well as pH values. Application of sonication to soy protein isolate films solution significantly increased tensile strength and its elongation at break.